Altered core and skin temperature responses to endurance exercise in heart failure patients and healthy controls. (29th August 2020) - Benda, Nathalie MM; Eijsvogels, Thijs MH; Van Dijk, Arie PJ; Bellersen, Louise; Thijssen, Dick HJ; Hopman, Maria TE
Abstract: Background: Exercise training represents a central aspect of rehabilitation of heart failure patients. Previous work on passive heating suggests impaired thermoregulatory responses in heart failure patients. However, no previous study directly examined thermoregulatory responses to an exercise bout, that is, active heating, as typically applied in rehabilitation settings in heart failure. Design: Cross-sectional observational study to compare changes in core body temperature ( T core) and skin temperature ( T skin) during exercise between heart failure patients and controls. Methods: Fourteen heart failure subjects (65 ± 7 years, 13:1 male:female) and 14 healthy controls (61 ± 5 years, 12:2 male:female) were included. T core (telemetric temperature pill) and T skin (skin thermistors) were measured continuously during a 45-min cycle exercise at comparable relative exercise intensity. Results: T core increased to a similar extent in both groups (controls 1.1 ± 0.4℃, heart failure patients 0.9 ± 0.3℃, 'time*group': p  = 0.15). T skin decreased during the initial phase of exercise in both groups, followed by an increase in T skin in controls (1.2 ± 1.0℃), whilst T skin remained low in HF patients (−0.3 ± 1.4℃) ('time*group': p  < 0.001). Furthermore, we found that a given change in T core was associated with a smaller increase in T skin in heart failure patients compared with controls. When comparing heart failure patients and controls who performed exercise at similar absolute workload, between-group differences disappeared ( p -values > 0.05). Conclusion: Heart failure patients and controls show comparable exercise-induced increase in T core, whilst heart failure patients demonstrate altered T skin responses to exercise and attenuated elevation in T skin per increase in T core. These impaired thermoregulatory responses to exercise are, at least partly, explained by the lower absolute workload and lower physical fitness level in heart failure patients.